(untitled) (Journal of the College of Basic Education, 2023)
Today, the media has become a force that has social dimensions as much as it has political power.economic and cultural media. Today, the media convey to us information, opinions, ideas, and trends.Through its communication activity, customs and traditions are transmitted and prevailing values in society are reinforced.Individuals will use the media for a variety of purposes, achieving different gratifications, and spending time with it.Fun times (1). Hence, satellite channels (Arab and foreign) sought to attract viewers.to view its programs through its endeavor to develop its software materials in general and the serviceinformation in particular. The press (news) scoop was the prominent feature in thischannels by focusing on very exciting news, in addition to providing explanations about theseevents, and it (the channels) played an important role by transmitting its broadcasts to all recipientsby direct broadcast. (2)